Analysis of Grammatical Errors in English-Indonesian Translation - Ryan Purnomo (Yayasan Pendidikan Intan Cendekia, 2022)
This research is aimed to analyze the ability of the students on translating English text into Indonesian and to identify the types of students' grammatical errors in translating English text into Indonesian. In this study, the authors used a qualitative approach. The research instrument that the authors used is a written test. Each student is instructed to translate the English text into Indonesian. The steps that the authors took are analyzing the data, classifying errors based on the type of error, reconstructing the correct form of the error, and calculating the percentage. The research method that is used to analyze college student errors is the qualitative description method. After analyzing the students’ translations, the result is “Add a word” error (14.86%) is the highest error, “to infinitive” and “Possessive pronoun” is the lowest errors (0.31%).